Trigonometry - Lial, Margaret L.; Hornsby, E. John; Schneider, David I. (Massachusetts : Addision-Wesley Publishing Company, 1997)
Trigonometry, Sixth Edition, is written for students in a traditional college trigonometry course. We assume students have had at least one course in algebra. Geometry is a desirable prerequisite, but many students reach trigonometry with little or no background in geometry. Because of this, we explain the necessary ideas from geometry as needed. Although this book is intended for a traditional course, we have acknowledged the growing interest in using graphing calculators to augment and deepen the concepts typically presented in trigonometry.
Chapter 1. The trigonometric functions -- Chapter 2. Acute angles and right triangles -- Chapter 3. Radian measure and the circular functions -- Chapter 4. Graphs of the circular functions -- Chapter 5. Trigonometric identities -- Chapter 6. Inverse trigonometric functions and trigonometric equations -- Chapter 7. Applications of trigonometry and vectors -- Chapter 8. Complex numbers and polar equations -- Chapter 9. Exponential and logarithmic functions
Includes index.
Keywords: TRIGONOMETRY -- DATA PROCESSING